THE MANAGEMENT CLOSE REDUCTION OF MANDIBULAR FRACTURE IN PEDIATRIC PATIENT: A CASE REPORT: PERAWATAN REDUKSI TERTUTUP FRAKTUR MANDIBULA PADA ANAK: LAPORAN KASUS - Yanti, Melva Novi; Tasman, Abel; Fathurachman, Fathurachman (Dentika: Dental Journal, 2016)
Mandibular fractures are less common in children compared to adults, due to a number of factors including the anatomical complexity of mandibular development in a child. This article aims to discuss the treatment’s principle of mandibular fractures differ from that of adults due to concerns regarding mandibular growth and development of dentition. A case of a 7-year old boy with fracture of the left mandibular corpus that sinistra region was treated with a closed reduction method using gunning splints with circumferential mandibular wires. On the sixth week after surgery, the circumferential mandibular wiring and splint were removed. From clinical examination there was no edema; no oral mucosal abnormalities were found; no teeth mobility; and no step displacement at corpus mandibular sinistra region. The treatment’s goal is to restore the structures from the broken bone to its pre-injury position as non-invasively as possible with minimal residual esthetic and functional impairment.